Relationship Marketing as an Effective Promotional Tool of Yoga Marketing in the Urban Indian Market : An Empirical Study - Giri, Arunangshu; Pandey, Mrinalini (Indian Journal of Marketing, 2016)
Yoga practices help to maintain a healthy living of physical, mental, and spiritual faculties. Different yogic postures keep our body in a proper condition by normalizing blood pressure, cholesterol levels, and boosting the immune system. So, it is required to market yoga services by implementing proper promotional tools in the present scenario. Relationship marketing helps to establish strong social, economic, and technical ties with customers. It decreases the transaction time and related costs. It creates a mutually profitable business relationship between customers and service providers. Initiation for yoga promotion is to be supported with relationship marketing as effective promotional tool for sustainable development of the yoga market. The purpose of this study was to examine the impact of relationship marketing on customer loyalty in the yoga sector. Maintaining the customer loyalty in the yoga sector is important to attract new potential customers in urban India to fulfill customers’ expectations related to their health care. Customer loyalty can be increased by adopting different significant strategies in yoga promotion through relationship marketing. Understanding of customer behaviour in the relationship-building process of a yoga organization is important to retain and attract potential customers. This study focused on the influences of different factors in the relationship-building process on customer loyalty in the context of yoga marketing in urban India. This study emphasized the marketing literature on the relationship development model for customer benefits. The findings discussed the effectiveness of relationship marketing as yoga promotional tools in the Indian urban market.